2017
DOI: 10.1002/anie.201700417
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Activated, Palladium Nanoparticle Catalyzed, Ultrafast Cross‐Coupling of Organolithium Reagents

Abstract: The discovery of an ultrafast cross-coupling of alkyl- and aryllithium reagents with a range of aryl bromides is presented. The essential role of molecular oxygen to form the active palladium catalyst was established; palladium nanoparticles that are highly active in cross-coupling reactions with reaction times ranging from 5 s to 5 min are thus generated in situ. High selectivities were observed for a range of heterocycles and functional groups as well as for an expanded scope of organolithium reagents. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 54 publications
0
49
0
Order By: Relevance
“…Recent advancements in the cross‐coupling of hard organometallic nucleophiles have been accelerated by the design of reactive catalysts with very high turnover frequencies . Published work on the coupling of organolithium reagents offers new insights into the active palladium catalyst.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advancements in the cross‐coupling of hard organometallic nucleophiles have been accelerated by the design of reactive catalysts with very high turnover frequencies . Published work on the coupling of organolithium reagents offers new insights into the active palladium catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…An interesting article for the biaryl synthesis by homo‐ and hetero‐Kumada couplings in water has also been reported . Feringa and co‐workers have reported the use of Pd‐phosphine catalysts for the coupling of organolithium reagents and found that, despite high turnover frequencies, coupling below −10 °C was not feasible …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melting points were measured on a Büchi Melting Point B‐540. Compounds 38 , 40 ,[33b] 42 , 48 , 50 and 52 are literature‐known. Therefore, merely GC‐MS measurements were conducted to confirm their formation during the reactions.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, Feringa et al. reported an ultrafast cross‐coupling of alkyl‐ and aryllithium reagents with a range of aryl bromides in the presence of both catalytic palladium nanoparticles and O 2 . The cross‐coupling of arylbromides with MeLi gave good to excellent yields with good functional group tolerance (Table ).…”
Section: Methylation By Using Conventional Reagentsmentioning
confidence: 99%